Asuhan Kebidanan Continuity Of Care NY. N 24 Tahun di Klinik Dharma Wahyu Agung - Pirawati (Universitas Ngudi Waluyo, 2023)
The period of pregnancy, childbirth, postpartum, neonate is a physiological condition that is likely to threaten the life of the mother, baby and even cause death. One of the efforts that can be made is to implement a comprehensive midwifery care model that can optimize the detection of high risk maternal neonates. Methods of midwifery care at the Dharma Wahyu Clinic Agung Bedono, Ambarawa, Semarang Regency, Central Java and through home visits. The midwifery care provided to Mrs. In Mrs.